Thermal field modeling and characteristic analysis based on oil immersed transformer - Gao, Chao; Huang, Lijun; Feng, Yuhui; Gao, Erya; Yang, Zhongqing; Wang, Kai (Frontiers in Energy Research, 2023)
Oil-immersion transformer plays an important role in the operation of power system, and its reliable operation is the basis of the safe and economic operation of power system. Transformer internal failure will not only cause the transformer to stop, but also damage, affecting the proper operation of the power system. Therefore, it is necessary to carry out effective detection and protection for transformer faults. The transformer is often in a high-temperature and high-pressure environment during its operation, so it is difficult to effectively and accurately protect the transformer from failure in the harsh working environment. Because the existing methods can not detect and protect the faults of transformer equipment sensitively and accurately, based on this, this paper carried out the research on the detection and protection of oil immersed transformer. By analyzing the calculation results, the relationship between the temperature rise of the transformer structure and the ambient temperature is discussed. This provides a reference for making the starting strategies of transformers in different environments, and helps to avoid mechanical structure damage and insulation aging damage caused by temperature.